The Vividness of Happiness in Dynamic Facial Displays of Emotion - Becker, D. Vaughn (Public Library of Science, 2012)
Rapid identification of facial expressions can profoundly affect social interactions, yet most research to date has focused on static rather than dynamic expressions. In four experiments, we show that when a non-expressive face becomes expressive, happiness is detected more rapidly anger. When the change occurs peripheral to the focus of attention, however, dynamic anger is better detected when it appears in the left visual field (LVF), whereas dynamic happiness is better detected in the right visual field (RVF), consistent with hemispheric differences in the processing of approach- and avoidance-relevant stimuli. The central advantage for happiness is nevertheless the more robust effect, persisting even when information of either high or low spatial frequency is eliminated. Indeed, a survey of past research on the visual search for emotional expressions finds better support for a happiness detection advantage, and the explanation may lie in the coevolution of the signal and the receiver.